Justice delayed is justice denied: Protecting Miners against Occupational injuries and diseases: Comments on Mankayi v Anglogold Ashanti Ltd 2011 32 ILJ 545 (CC) - Tshoose, CIarence (Potchefstroom Electronic Law Journal, 2017)
In the Mankayai v Anglogold Ashant Ltd 2011 32 ILJ 545 (CC) the Constitutional Court was called upon to give meaning and content by interpreting the provision of section 35 of Compensation for Occupational Injuries and Diseases Act 130 of 1993 (COIDA) and section 100(2) of the Occupational Diseases in Mines and Works Act 78 of 1973. The Court had to determine if the employee common-law right of recourse against his employer in cases where he sustained occupational diseases is extinguished by virtue of section 35(1) of COIDA. The purpose of this case note is twofold: firstly, it analyses the decision of the Constitutional Court in the Mankayi case; secondly, the case note looks at the significance of the Mankayi case for the system of occupational health and safety in South Africa. In conclusion, the contribution explores the need for the introduction of a unified system which will address issues of occupational health and safety in a coordinated and unified manner.